Synthesis and characterization of hydroxyapatite/SiO2/gelatin composites as bone scaffold candidates - Wahda, Indah; Syaharuddin Kasim; Maming; Hasnah Natsir; St Fauziah; Yusafir Hala; Andi Muhammad Anshar; Usman, Andriani; Windasari; Indah Raya (Communications in Science and Technology, 2024)
This study aims to determine the characteristics of hydroxyapatite/SiO2/gelatin composites to fulfil the bone scaffold standards. XRF analysis showed that limestone has a high CaO content of 92.89%, allowing it be used for hydroxyapatite synthesis. The wet precipitation method was used to synthesize hydroxyapatite; meanwhile, the freeze-drying method was used to synthesize the hydroxyapatite/SiO2/gelatin scaffold. FTIR analysis confirmed the characteristic peaks, which indicated the presence of compounds of hydroxyapatite (OH- and PO43-), SiO2 (Si-OH and Si-O-Si), and gelatin (N-H, C-H, and C=O). XRD analysis showed 98.1% hydroxyapatite phase and 1.9% SiO2 phase and SEM analysis showed a scaffold pore size of 155-218?m, optimal for cell attachment. Furthermore, mechanical testing resulted in a compressive strength of 1.71 MPa and porosity testing resulted in a porosity of 75%. This characterization showed the potential use of hydroxyapatite/SiO2/gelatin composites as bone scaffolds. This research can enable further development of scaffold materials in the field of tissue engineering.